SOCIOSEMIOTIC APPROACH IN TRANSLATING INDONESIAN FOLKLORES INTO ENGLISH (Action Research in the Translation Class of English Department) - Hartono, Rudi (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2014)
This research was done based on the urgent need to improve studentsâ translation quality in their translation practice, particularly in translating Indonesian folklores into English. In relation to this research background, the Sociosemiotic Approach was applied in solving the problems. The research was conducted in the translation class that involved 20 sixth semester students of English Department of Semarang State University. The research method used was the Classroom Action Research that followed four steps in one cycle: 1) Identifying the problems 2) Gathering the data 3) Interpreting the data, and 4) Acting the evidence. The data were taken from the studentsâ translation work, field notes, interviews and questionnaires. The data obtained were analyzed by using descriptive qualitative analysis. Based on the result of research it was found that the application of Sociosemiotic Approach improved studentsâ translation quality. Qualitatively the studentsâ translation products were more natural, communicative, and accepted culturally in English terms. Quantitatively the average score of their translation products increased from 69.65 to 82.15. It means that there was a significant improvement before and after applying the Sociosemiotic Approach with the progress score up to 12.55.